1994
DOI: 10.1002/nt.2620020108
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies of the venom of an Australian bulldog ant (Myrmecia pyriformis)

Abstract: The purpose of this study was to examine some of the pharmacological actions of venom from the Australian bulldog ant Myrmecia pyriformis. M. pyriformis venom was prepared by extraction of venom sacs in distilled water and centrifugation to remove insoluble material. Venom (2 micrograms/ml) produced a biphasic response of isolated guinea-pig ileum, i.e., an initial rapid contraction followed by a slower prolonged contraction. The histamine antagonist mepyramine (0.1 microM) inhibited the first phase of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In South Eastern Australia around 2.7% of the population are allergic to Myrmecia pilosula venom, with approximately 50% of allergic people experiencing life-threatening reactions (Brown et al, 2003). The toxicity of the venom appears to result from the presence of a variety of histamine-like, haemolytic and eicosanoid-releasing factors, peptides such as pilosulins, and enzymes including phospholipases, hyaluronidase, and phosphatases (Matuszek et al, 1994a(Matuszek et al, , 1992(Matuszek et al, , 1994bMcGain and Winkel, 2002).…”
Section: Pilosulinsmentioning
confidence: 94%
“…In South Eastern Australia around 2.7% of the population are allergic to Myrmecia pilosula venom, with approximately 50% of allergic people experiencing life-threatening reactions (Brown et al, 2003). The toxicity of the venom appears to result from the presence of a variety of histamine-like, haemolytic and eicosanoid-releasing factors, peptides such as pilosulins, and enzymes including phospholipases, hyaluronidase, and phosphatases (Matuszek et al, 1994a(Matuszek et al, , 1992(Matuszek et al, , 1994bMcGain and Winkel, 2002).…”
Section: Pilosulinsmentioning
confidence: 94%
“…Cavill et al showed that (i) the venom of M. gulosa is primarily polypeptidic [with a small amount of histamine (~2%)], (ii) at least eight distinct polypeptide fractions could be separated by electrophoresis, and (iii) multiple distinct biological activities are associated with some of these polypeptide fractions, namely, hyaluronidase, kinin-like, and hemolytic activity. Further studies have since revealed that the venoms of other species of Myrmeciinae are similarly polypeptidic (6)(7)(8)(9)(10)(11)(12), as are those of ants of at least seven other subfamilies, namely, Amblyoponerinae (13), Dorylinae (14), Ectatomminae (15), Myrmicinae (16), Paraponerinae (17), Ponerinae (18), and Pseudomyrmecinae (19).…”
Section: Introductionmentioning
confidence: 99%
“…The venom contains histamine-like activity, a heat-sensitive haemolytic factor and causes the release of cyclooxygenase products 7. We felt it was unlikely that the venom was responsible for this patient's ocular presentation because it was unilateral, presented some time after the sting and has not been reported previously despite bull ant stings being relatively common.…”
Section: Discussionmentioning
confidence: 83%